The Influence Of HR Planning, Work Placement And Career Development On Employee Performance Through Work Motivation As An Intervening Variable In The Regional Civil Service Agency Of West Sumatra Province - Septivoni; Dharma, Robby; Mary, Hilda (Riset Sinergi Indonesia, 2024)
The Regional Civil Service Agency of West Sumatra Province is a government institution that has the main task to assist the governor in the implementation of regional civil service. The purpose of this study is to determine and analyze the effect of HR Planning, Work Placement and Career Development on Employee Performance through Work Motivation as an Intervening Variable. The research method used is quantitative research. The sample size of this study was 74 respondents and used SEM analysis tools with SmartPLS 3. In the data collection technique in this study by distributing questionnaires using Likert scale. The results showed that directly the most dominant variable, namely Career Development, had a positive and significant effect on Work Motivation. Therefore, evidenced by the increasing career development promised by the company, employee motivation will also increase. Furthermore, HR Planning has a positive and significant effect on Employee Performance, it shows that there is careful planning for HR, so employee performance will increase. While indirect testing for the most dominant variables states that career development has a positive and significant effect on employee performance through work motivation, that the existence of good career development opportunities will strengthen employee performance and increase employee motivation. Conversely, if career development is not good for its performance, work motivation will lower the level of employee concern regarding the progress of the company. Employees who care about the progress of the company will be more motivated to work so as to form stronger performance.